1989
DOI: 10.1179/bjo.16.4.259
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age at Diagnosis on the Complexity and Outcome of Treatment of Palatally Ectopic Canines

Abstract: This study examined the records of 218 patients from the 5-year period 1979–1983 who were treated for palatally ectopic canines in the Glasgow Dental Hospital. It tested the hypothesis that there was a relationship between the age of the patient at diagnosis, and the complexity and outcome of treatment. Whilst the age of the patient had no influence on the complexity of the treatment required, it had a significant effect on the outcome since it was related to the number of failed appointments and the likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…26 However, it is generally agreed that the optimal time for surgical exposure and orthodontic alignment is during adolescence. [27][28][29] Factors which determine whether to consider surgically exposing and orthodontically aligning the ectopic permanent canine are as follows:…”
Section: Surgical Exposure and Orthodontic Alignment (Sign Grade C)mentioning
confidence: 99%
“…26 However, it is generally agreed that the optimal time for surgical exposure and orthodontic alignment is during adolescence. [27][28][29] Factors which determine whether to consider surgically exposing and orthodontically aligning the ectopic permanent canine are as follows:…”
Section: Surgical Exposure and Orthodontic Alignment (Sign Grade C)mentioning
confidence: 99%
“…Smatralo se da ovaj zub mora mnogo više da putuje pre izbijanja nego ostali, te da se zato lakše "izgubi na putu" [5]. Smatralo se da ovaj zub mora mnogo više da putuje pre izbijanja nego ostali, te da se zato lakše "izgubi na putu" [5].…”
Section: Teorije U Vezi S Palatinalnim Položajem Gornjeg Očnjakaunclassified
“…Novija istraživanja su čak pokazala da je mogućnost pojave palatinalno impaktiranog očnjaka mnogo veća kad postoji višak prostora u luku [5,6]. Kao što je već opisano, stalni lateralni sekutić u razvoju smešten je lingvalno od zubnog luka.…”
Section: Teskobaunclassified
“…Defining orthodontic treatment complexity is modulated by the interaction between factors related to patient's compliance, clinician's skill and experience, and malocclusion characteristics and severity. 3 , 8 - 11 More specifically, previous studies have reported that there seems to be a correlation between orthodontists' perception of severity of malocclusion characteristics and treatment complexity. 11 - 14 In this study, we focus on the correlation between severity and complexity because only malocclusion characteristics and their severity can be measured more or less objectively before treatment.…”
Section: Introductionmentioning
confidence: 99%